Pengaruh Aset Lancar, hutang Jangka Panjang, Ekuitas, Laba Terhadap Kinerja Keuangan Perusahaan Manufaktur di BEI - Ima Andriyani; Sari Sakarina; Suharti Suharti; Herman Efrizal (UNIVED Press, 2022)
This study aims to find out and prove the Effect of Current Assets, Long-Term Debt, Equity, Net Profit and Profit Hold Against the Financial Performance of Manufacturing Companies in the Industrial Sector Food and Beverage Consumables Listed on the Indonesia Stock Exchange either Simultaneously or Partially. The results of this study indicate that, There is the Effect of Current Assets, Long-Term Debt, Equity, Net Profit and Retained Earnings Together - on Financial Performance of Manufacturing Companies in the Industrial Sector of Food and Beverage Consumables Listed on the Indonesia Stock Exchange, There Are Effects of Current Assets Against Financial Performance of Manufacturing Companies in the Industrial Sector of Food and Beverage Consumables Listed on the Indonesia Stock Exchange. There are Effects of Long-Term Debt on Financial Performance of Manufacturing Companies in the Industrial Sector of Food and Beverage Consumables Listed on the Indonesia Stock Exchange. There Is No Effect of Equity on the Financial Performance of Manufacturing Companies in the Industrial Sector of Food and Beverage Consumables Listed on the Indonesia Stock Exchange. There Is No Effect of Net Profit on the Financial Performance of Manufacturing Companies in the Industrial Sector of Food and Beverage Consumables Listed on the Indonesia Stock Exchange in the Industrial Sector of Food and Beverage Consumables Listed on the Indonesia Stock Exchange in the Year.Efforts to improve management of asset assets, long-term debt, equity, net income and retained earnings to improve financial performance by using more efficient and optimal current assets, minimizing the use of long-term debt, using optimal equity, increasing related net income sector with an increase in the sales sector and attention to the amount of dividend distribution to shareholders for the company's retained earnings.